THE IMPORTANCE OF TRUST IN TEACHER-STUDENT COMMUNICATION IN SCHOOL - Butar Butar, Raja; Alfonsius (FEB Universitas Sam Ratulangi Manado, 2025)
The communication between teachers and students can be considered as an important type of communication since it naturally involves the topic of education, life, knowledge, etc., especially when it is conducted in the school scope. Trust has been an element in communication, which promotes understanding and collaboration between the parties involved. It is important to finally realize that trust is a powerful element for teachers and senders to achieve intended goals. This study aims to elaborate, share and emphasize that teacher-student communication in school can be deemed effective and proper, when trust is put as the main element inside it. This study leans on the methodology of literature review where the process of summarizing, synthesizing and/or critiquing the literature are combined, identifying the developments in the topic of trust, with focus on its use between teachers and students in school. It is true that trust is of high importance for teachers and students in doing communication when they are in school, and this situation also assures that trust is type of capital that is generally essential for interaction between parties.